An Arrayed Micro‐glutamate Sensor Probe Integrated with On‐probe Ag/AgCl Reference and Counter Electrodes. Issue 3 (23rd January 2018) - Hoa, Le Ngoc Quynh; Chen, Hong‐Ru; Tseng, Tina T.‐C.
Abstract: Complete all‐in‐one multi‐arrayed glutamate (Glut) sensors have been constructed on a silicon‐based micromachined probe composed of micro‐platinum (Pt) working electrodes, a micro‐silver/silver chloride (Ag/AgCl) reference electrode (RE), and a micro‐Pt counter electrode (CE). The OCP shift of the electrodeposited Ag/AgCl on‐probe micro‐reference electrode compared with a Ag/AgCl wire is <0.1 mV/h. The composition ratio of Ag, Cl, and Pt on the electrodeposited on‐probe micro‐reference electrode is observed to be 1.00 : 0.48 : 0.02 analyzed by EDS. The miniaturized amperometric Glut biosensors were constructed on working electrode sites (electrode area: ∼8.5×10 −5 cm 2 ) of the microprobe modified with glutamate oxidase (GlutOx) enzyme layers for the selective, fast, and continuous detection of L‐glutamate. The sensor selectivity towards common electroactive interferents has been improved significantly by coating the electrode surface with perm‐selective polymer layers, overoxidized polypyrrole (PPY) and Nafion®. The sensitivity, detection range, and response time of the proposed all‐in‐one Glut biosensors are 204.7±5.8 nA μM −1 cm −2 ( N =5), 4.99–109 μM, and 2.7±0.3 sec, respectively and no interferent signals of AA and DA were observed. The sensor can be reused over 19 times of continuous repetitive operation (total measurement time: ∼4 hours) and the sensor sensitivity can retain up to four weeks of storage. Abstract :